Performance assessment: Teachers beliefs and practices in higher education - Lukluk Argita Munif; Endang Fauziati; Sri Marmanto (Intelektual Pustaka Media Utama, 2019)
In educating the students, teachers’ beliefs on teaching and learning influenced not only on what to teach and how to do it, but also on how to assess their students. Education has a goal that students can apply the knowledge gained in real world activities. Through assessment process, it helps them to understand their strengths and weaknesses of their abilities development. This research aims to find out teachers’ beliefs about performance assessment and how they use it to assess their students in one of public college under The Ministry of Industry in Indonesia. Data findings are obtained by using interviews, observation and document analysis conducted on T1 and T2 as the participants. Researcher used the five elements of performance assessment to make the instruments and analyze the findings. Results indicated that there were differences between what they say and what they do. The differences appeared because of the theories they knew, their own knowledge and experiences they have in teaching.